2000
DOI: 10.1002/1097-4644(20000915)78:4<595::aid-jcb9>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Selenoorganic compound, ebselen, inhibits nitric oxide and tumor necrosis factor-? production by the modulation of Jun-N-terminal kinase and the NF-?b signaling pathway in rat Kupffer cells

Abstract: In response to the bacterial endotoxin, LPS, Kupffer cells are induced to express NO and TNF-alpha. These compounds are involved in hepatic inflammation/injury, especially that associated with endotoxic shock. In this study, we demonstrate that ebselen (2-phenyl-1,2-benzisoselenazol-3[2H]one), a selenoorganic compound, blocks LPS-induced NO and TNF-alpha production by cultured rat liver Kupffer cells. LPS can activate both the NF-kappaB signaling pathway and MAPK signal transduction pathways such as JNK and p3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…EGCG, the major polyphenol present in green tea, has been reported to inhibit the induction of iNOS expression in the RAW264.7 murine macrophage cell line (32). Ebselen, an organic selenium compound, can inhibit LPS-induced NO production in rat liver Kupffer cells (33). Ebselen and dexamethasone reportedly protect mice from galactosamine and Salmonella-LPS-induced hepatitis (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGCG, the major polyphenol present in green tea, has been reported to inhibit the induction of iNOS expression in the RAW264.7 murine macrophage cell line (32). Ebselen, an organic selenium compound, can inhibit LPS-induced NO production in rat liver Kupffer cells (33). Ebselen and dexamethasone reportedly protect mice from galactosamine and Salmonella-LPS-induced hepatitis (34).…”
Section: Discussionmentioning
confidence: 99%
“…Ebselen and dexamethasone reportedly protect mice from galactosamine and Salmonella-LPS-induced hepatitis (34). Dexamethasone, EGCG, and ebselen may reduce iNOS gene expression through NF-B signaling, either by up-regulating I-B␣ or inhibiting NF-B (32,33,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to determine whether this reflects in vivo mechanisms by which increases in dietary Se affect macrophage activation. Experiments using the selenoorganic compound, ebselen, showed that this compound inhibited NO, Cox-2, and TNF-a in rat Kupfer cells, which are the resident macrophages of the liver (229). This suggests that small-molecular-weight selenocompounds influence redox status in these in vitro experiments, but the role of these compounds versus selenoproteins in vivo needs to be considered.…”
Section: The Effects Of Se Intake On Camentioning
confidence: 99%
“…One example is the inhibition histone deacetylase (HDAC) activity in diffuse large B-cell lymphoma cell lines by methylseleninic acid and the toxic effects this may exert in chemoprevention (125). In addition, some studies have used the selenoorganic compound, ebselen, to show that macrophage and dendritic cell functions are affected by this smallmolecular-weight selenocompound (156,229). However, there are very few studies that investigate the effects of selenocompounds on inflammation or immunity, and most of the data regarding the biological activity of Se is related to its incorporation into selenoproteins.…”
Section: Bioactive Forms Of Se and Their Effectsmentioning
confidence: 99%
“…22 Semiquantitative RT-PCR assay was basically performed as described. [22][23][24] The PCR primers were constructed based on the published nucleotide sequences of the rat TNF-␣ gene 25 (GenBank accession number, L00981) [5Ј-CCC AGA CCC TCA CAC TCA GA-3Ј (sense); 5Ј-GCC ACT ACT TCA GCA TCT CG-3Ј (antisense)]; the rat iNOS gene 26 (GenBank accession number, U03699) [5Ј-TGG GCA CCG AGA TTG GAG TC-3Ј (sense); 5Ј-AAA TAC CGC ATA CCT GAA GG-3Ј (antisense)]; and the rat glycerol aldehyde 3-phosphate dehydrogenase (GAPDH) gene 27 (GenBank accession number, M17701) [5Ј-GGC AAG TTC AAT GGC ACA GT-3Ј (sense); 5Ј-AAG GTG GAG GAA TGG GAG TT-3Ј (antisense)]. In the competitive PCR of TNF-␣, iNOS, or GAPDH, the TNF-␣ cDNA sequence with a 74-base pair (bp) deletion, the iNOS cDNA sequence with an 82-bp deletion, or the GAPDH cDNA sequence with a 146-bp deletion, respectively, was used as the competitor DNA sequence.…”
Section: Semiquantitative Reverse Transcription (Rt)-polymerase Chainmentioning
confidence: 99%